A framework for distributed key management schemes in heterogeneous wireless sensor networks - Lu, K.; Qian, Y.; Hu, J. (2006 IEEE International Performance Computing and Communications Conference, 2006)
Key management is a major challenge in the design and deployment of secure wireless sensor networks. A common assumption in most distributed key management schemes is that all sensor nodes have the same capability. However, recent research work has shown that the connectivity and lifetime of the sensor network can be substantially improved if a small number of sensor nodes have more energy capacity and transmission capability. Therefore, how to utilize these heterogeneity features to design a good distributed key management scheme has become an important issue and needs to be explored. In this paper, we propose a framework for key management schemes in distributed wireless sensor networks with heterogeneous sensor nodes. We show by simulations analysis that, with a small number of heterogeneous nodes, the wireless sensor network can achieve higher key connectivity and higher resilience